(3UfGYI GdJGQjNs - (3aQGj, SJjafs; (3YHO GdYGd, eMeOs; (3eMehO, ESQGAs ((3GdbGgQIs (3YUjQ GdcJHs, 2024)
(3eGPG dh de jhdO COhda gJdQ? eGjcd jGfL eDpqQN aj LGeYI cGeHQOL ojced CWQhMJg Yf MjGI COhda gJdQ aj THGHg, JJHOd MjGJg YfOeG jbGHd djh ShcQeGf, YGde ajRjGA CdeGfj YLhR fLG ef GdghdhchSJ JWGQOg dYfI GdPfH hGdYGQ hGdOe GdJj hQKgG Yf hGdOg(B. (3jNhVGf ekYG eZGeQI eKGdjI LGeMI aj eMGhdI dJZjjQ eLQi GdJGQjN heMh COhda gJdQ ef GdhLhO(B. (3hHfLGM JLQHJgeG ojNdb YGde LOjO TLGY CaVd ef YGdefG aj HYV GdfhGMj, hdcfg CHTY aj eYXe GdfhGMj(B. (3LYdrJ JLQHI aQGj GdJGQjNjI UfGYI GdJGQjN CaVd QhGjGJg hCTOgG LehkMG hJCKjkQG(B. (3hgh GdcJGH GdChd dg GdPj JOhQ eYXe CMOGKg aj CeQjcG(B. (3bUI eTpqhbI JJNddgG deSI aQGj GdWQjaI hGdeVMcI, aj JNoqjd eSJbHdj eHfj Ydi CMO CcKQ GdhbGFY GdHTQjI ShOGhjIs
(3gPG GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdGfLdjRjIs
Keywords: (3GdCOH GdCfLdjRjs; (3GdCOH GdeJQLes